Klebsiella pneumoniae Causing Liver Abscess, Endophthalmitis, and Cavitary Pneumonia. Issue 4 (July 2020) - Doke, Purwa; Soman, Rajeev; Purandare, Bharat; Diwan, Arundhati; Mahajan, Sumeran; Panchakshari, Shweta
Abstract : Abstract: Klebsiella pneumoniae is a common pathogen associated with hospital and healthcare-acquired infections. Hypervirulent K. pneumoniae can cause community-acquired pyogenic liver abscess in patients without previous history of liver disease with metastasis to distant sites. We report a case of hypervirulent K. pneumoniae bacteremia causing hepatic abscess, endophthalmitis, and cavitary pneumonia in a diabetic male.